If Madness Could Speak. Reconstituting the Discourse of Madness and its Relation to Truth - Lepage-Richer, Théo (Rivista Italiana di Filosofia del Linguaggio, 1970)
Ahonen, Marke (2014), Mental Disorders in Ancient Philosophy, Springer, Berlin. Derridda, Jacques (1963), «Cogito et histoire de la folie» in Revue de Métaphysique et de Morale, n. 68.4, pp. 460-494. Descartes, René (1641), Meditationes de prima philosophia, Michaelem Soli, Paris (Méditations métaphysiques, in Œuvres choisies de Descartes, Garnier Frères, Paris 1876).   Drake R., Whitley R. (2010), «Recovery: A Dimensional Approach», in Psychiatric Services, n. 61.12, pp. 1248-1250. Drake R., Whitley R., (2014), «Recovery and Severe Mental Illness: Description and Analysis», in CanJPsychiatry, n. 59.5, pp. 236–242. Foucault, Michel (1961), Histoire de la folie à l’âge classique, Gallimard, Paris 2012 (Madness and Civilization: A History of Insanity in the Age of Reason, transl. by Richard Howard, Random House, New York 1965). Foucault, Michel (1967), L’archéologie du savoir, Gallimard, Paris 2016. Foucault, Michel (1982-83), Le Gouvernement de soi et des autres. Cours au Collège de France. 1982-1983, Éditions du Seuil, Paris 2008 (The Government of Self and Others: Lectures at the Collège de France, transl. by Graham Burchell, Picador, New York 2011). Grube, George M. A. (1954), «Greek medicine and the Greek genius», in Phoenix, n. 8.4, pp. 123-135. Jansman-Hart, Erika et al. (2011), «International Trends in Demand for Forensic Mental Health Services International», in Journal of Forensic Mental Health, n. 10.4, pp. 326-336. Kenny, Anthony (1973), Anatomy of the Soul: Historical Essays in Philosophy of Mind, Basil Blackwell, Oxford. Nietzsche, Friedrich (1889), Götzen-Dämmerung, oder, Wie man mit dem Hammer philosophiert, Verlag Von C. G. Naumann, Leipzig (Twilight of the Idols, or, How to Philosophize with a Hammer, in The Anti-Christ, Ecce Homo, Twilight of the Idols and Other Writings, transl. by Judith Norman, Cambridge University Press, Cambridge 2005). Plato, Alcibiades in Plato: Complete Works, edited by John M. Cooper, Hackett Publishing, Indianapolis 1997. Plato, Apology in Plato: Complete Works, Hackett Publishing, Indianapolis 1997. Plato, Cratylus in Plato: Complete Works, Hackett Publishing, Indianapolis 1997. Plato, Euthydemus in Plato: Complete Works, Hackett Publishing, Indianapolis 1997. Plato, Euthyphro in Plato: Complete Works, Hackett Publishing, Indianapolis 1997. Plato, Laws in Plato: Complete Works, Hackett Publishing, Indianapolis 1997. Plato, Phaedrus, edited by Robin Waterfield, Oxford University Press, Oxford 2002. Plato, Republic in The Republic of Plato, edited by Allan Bloom, HarperCollins, New York 1968. Plato, Timaeus in Plato: Complete Works, Hackett Publishing, Indianapolis 1997. Seeskin, Kenneth (2008), «Plato and the origin of mental health», in International Journal of Law and Psychiatry, n. 31, pp. 487-494. Seto, Michael et al. (2001), Demands for forensic services in the province of Ontario, Ontario Mental Health Foundation, Toronto. Veyne, Paul (1983), Les Grecs ont-ils cru à leurs mythes? Essai sur l'imagination constituante, Éditions du Seuil, Paris (Did the Greeks Believe in Their Myths? An Essay on the Constitutive Imagination, transl. by Paula Wissing, University of Chicago Press, Chicago 1988).